Life Motivation in Autobiography of Nick Vujicic Life Without Limits Literary Learning Perspective - Rifka Meluwu; Intama J. Polii; Mayske R. Liando (Syntax Corporation Indonesia, 2022)
This study describes Nick Vujicic's life motivation which includes extrinsic and intrinsic motivation to fulfill his life needs in his autobiography